An in silico toolbox for the prediction of the potential pathogenic effects of missense mutations in the dimeric region of hRPE65. (31st December 2023) - Poli, Giulio; Demontis, Gian Carlo; Sodi, Andrea; Saba, Alessandro; Rizzo, Stanislao; Macchia, Marco; Tuccinardi, Tiziano
Abstract: h RPE65 is a fundamental enzyme of the retinoid visual cycle, and many missense mutations affecting its expression or function are associated with a wide range of diseases. Many h RPE65 missense mutations lack a clear pathogenicity classification or are labelled as VUS. In this context, we recently developed a protocol based on µs-long molecular dynamics simulations to study the potential pathogenic effect of h RPE65 missense mutations. In the present work, the structure-based protocol was integrated with a h RPE65-tailored consensus bioinformatics strategy, named ConPath, that showed high performance in predicting known pathogenic/benign h RPE65 missense mutations. The combined strategy was used to perform a multi-level evaluation of the potential pathogenicity of 13 different h RPE65 VUS, which were classified based on their likelihood of pathogenic effect. The obtained results provide information that may support the reclassification of these VUS and help clinicians evaluate the eligibility for gene therapy of patients diagnosed with such variants.